PENGGUNAAN KARET ALAM PADA PEMBUATAN APRON UNTUK MESIN PEMINTALAN - Luftinor Luftinor (Jurnal Dinamika Penelitian Industri, 2010)
The Research aims to increase the use of natural rubber in the textile industry especially is ring spinning machine, the research done by varying the amount of apron manufacture of natural rubber (SIR 20), synthetic rubber (SBR), and filler materials (carbon black) in 3 levels of each treatment each 25 phr, 50 phr and 75 phr, obtained nine kinds of rubber compounds. The nine kinds of vulcanized rubber compounds to obtain finished goods apron, next physics test. Physical properties test results as a whole rubber apron almost meet quality standards, unless the results of hardness and elongation at break. Then all nine kinds of rubber is tested on ring spinning machine spinning in the process of making yarn polyster/cotton, yarn obtained to test quality yarns. The result of the overall yarn quality tests meet quality standards, except amount of ends breakages yarn test result. Optimal condition where rubber apron physic character the result and yarn quality approaches standard quality is got in apron uses rubber SIR 25 phr, rubber SBR 75 phr, carbon black and 75 phr, values obtained 79 shore A hardness, tensile strength 173 kg/cm2, modulus 132 kg/cm2, elongation at break 220%, tear strength 121 kg/cm2. And abration resistance DIN 122 mm3. Then the yarn quality obtained with Ne1 40,4 fineness, tensile strength per stand of 283,4 grams, a twist of  25.7, unevenness 13.3 U%, elongation at break 24.5 cm, and a mount of ends breakages per hour 4.